2014
DOI: 10.5977/jkasne.2014.20.2.341
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Blended Practicum Combined E-learning between Cooperative and Individual Learning on Learning Outcomes

Abstract: Purpose: This study was conducted to compare blended practicum with clinical and lab combined e-learning between cooperative and individual group on learning outcomes. Method: A total of 63 junior Nursing students were recruited from C University in G city from May, 2012 to June, 2012. Ten hours lab practicum for two weeks was provided for both two groups during the period of adult nursing practicum. Prior to blended practicum, e-learning was conducted. For cooperative group, two hours off line team learning w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…www.kan.or.kr 이슬기 · 신윤희 교육의 중요성이 어느 때 보다 강조되고 있다 [3]. 특히, 앞으로 환자 에게 안전한 간호를 제공해야 할 의무가 있는 간호학생의 정확한 기 본간호수기 수행은 필수적인 것으로 [1], 한국간호교육평가원(Korea [5].…”
unclassified
“…www.kan.or.kr 이슬기 · 신윤희 교육의 중요성이 어느 때 보다 강조되고 있다 [3]. 특히, 앞으로 환자 에게 안전한 간호를 제공해야 할 의무가 있는 간호학생의 정확한 기 본간호수기 수행은 필수적인 것으로 [1], 한국간호교육평가원(Korea [5].…”
unclassified
“…This might make South Korea a place where it is challenging to implement cooperative learning. However, cooperative learning has been attracting the attention of South Korean educators and is being actively studied in different levels from elementary to higher education, in diverse disciplines from science to nursing education (Choi et al. , 2014; Kim, 2018; Kim, 2021; Lee and Osman, 2021; Park, 2010a; Park, 2010b).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This might make South Korea a place where it is challenging to implement cooperative learning. However, cooperative learning has been attracting the attention of South Korean educators and is being actively studied in different levels from elementary to higher education, in diverse disciplines from science to nursing education (Choi et al, 2014;Kim, 2018;Kim, 2021;Lee and Osman, 2021;Park, 2010a;Park, 2010b). Kim (2018) investigated the effects of Korean Middle School students' relationship in a science class in which cooperative learning was employed and found that cooperative learning promoted interaction among students.…”
Section: South Koreamentioning
confidence: 99%
See 1 more Smart Citation
“…Practicum is a learning method that help student to understand more concept by direct interaction between student, instrument, and science material [2]. It also improves student intellectual skills by observation and gathering information.…”
Section: Introductionmentioning
confidence: 99%